Enhancing optical feedback interferometry with an integrated variable optical attenuator. - Arshad, Ayesha; Zabit, Usman; Bernal, Olivier; Deleau, Clement; Halir, Robert (My University, 2025)
Optical feedback interferometry is a promising technique for displacement sensing. Maintaining stable and precise optical feedback requires effective control of reflected light intensity. In this study, we propose an integrated on-chip OFI system featuring a variable optical attenuator (VOA) for dynamic feedback regulation. We develop a novel analytical model and, through a realistic attenuator design, demonstrate the system’s capability to achieve high-precision displacement measurements over a wide optical feedback parameter range (2 < C < 100) for target distances up to a few centimetres. These results highlight the potential of this approach for short-range applications with variable reflection conditions, such as MEMS characterisation.
Keywords: Interferometría; Medidas ópticas; Self-mixing interferometry; Laser sensor; Displacement sensing; Integrated optics; Silicon-on-Insulator